2022
DOI: 10.3389/fnhum.2022.872639
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Potential Mechanisms Supporting Low Intensity Focused Ultrasound for Neuromodulation

Abstract: Low intensity focused ultrasound (LIFU) has been gaining traction as a non-invasive neuromodulation technology due to its superior spatial specificity relative to transcranial electrical/magnetic stimulation. Despite a growing literature of LIFU-induced behavioral modifications, the mechanisms of action supporting LIFU's parameter-dependent excitatory and suppressive effects are not fully understood. This review provides a comprehensive introduction to the underlying mechanics of both acoustic energy and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 123 publications
(217 reference statements)
1
41
0
Order By: Relevance
“…The mechanisms of ultrasound neuromodulation have been extensively studied but not fully understood where ultrasound, as a mechanical pressure can act on mechanosensitive ion channels, has attracted much attention (31). Piezo is a mechanically sensitive ion channel that contains two isoforms, Piezo1 and Piezo2, of which Piezo1, is widely expressed in the central nervous system (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of ultrasound neuromodulation have been extensively studied but not fully understood where ultrasound, as a mechanical pressure can act on mechanosensitive ion channels, has attracted much attention (31). Piezo is a mechanically sensitive ion channel that contains two isoforms, Piezo1 and Piezo2, of which Piezo1, is widely expressed in the central nervous system (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…tFUS has become an emerging and attractive NIBS technique due to its high spatial resolution and deeper target of brain stimulation [ 127 ]. Although many animal trials have reported the benefits of tFUS for stroke [ 128 , 129 , 130 , 131 ], its application in post-stroke patients is still rare.…”
Section: Overview Of Neuromodulation and Nibsmentioning
confidence: 99%
“…The idea of LITFUS-induced inhibition in areas relevant for executing heightened affect regulation and cognitive control as an underlying mechanism is supported by LITFUS modelling approaches. Given the applied parameters (Table S1), modelling would predict inhibition on a neuronal level (29,30).…”
Section: Litfus For Human Affect Neuromodulationmentioning
confidence: 99%